Guernsey : Financial System Stability Assessment-Update. (IMF Staff Country Reports; Country Report, 2011)
Guernsey is a leading international insurance center in Europe. Its economy purely depends on the performance of the financial sector. As per the 2003 assessment under the Offshore Financial Center (OFC) program, it is found that the Guernsey Financial Services Commission (GFSC)'s powers have been strengthened in recent years and many recommendations of the 2003 Financial Sector Assessment Program (FSAP) have been implemented. The GFSC has developed a strategy for addressing banks' financial stability risks, but strong policy measures will be essential to deal with the potential vulnerabilities and challenges ahead.